2013
DOI: 10.1371/journal.pone.0056125
|View full text |Cite
|
Sign up to set email alerts
|

Simple SPION Incubation as an Efficient Intracellular Labeling Method for Tracking Neural Progenitor Cells Using MRI

Abstract: Cellular magnetic resonance imaging (MRI) has been well-established for tracking neural progenitor cells (NPC). Superparamagnetic iron oxide nanoparticles (SPIONs) approved for clinical application are the most common agents used for labeling. Conventionally, transfection agents (TAs) were added with SPIONs to facilitate cell labeling because SPIONs in the native unmodified form were deemed inefficient for intracellular labeling. However, compelling evidence also shows that simple SPION incubation is not invar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…Surface modifications play an important role in the direct interaction with cells and proteins present in the body fluids and culture medium [49,50]. Furthermore, depending on size, dosage, and exposure time, the nanoparticles can penetrate the biological membranes and reach the target site [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Surface modifications play an important role in the direct interaction with cells and proteins present in the body fluids and culture medium [49,50]. Furthermore, depending on size, dosage, and exposure time, the nanoparticles can penetrate the biological membranes and reach the target site [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…15,[71][72][73] The data and images shown in Figure 1 illustrate the high proportion of bone marrowderived mesenchymal stem cells labeled with SPIONs. In addition to the stem cell tracking, SPIONs have also been used to magnetically target stem cells to lesion sites, as described by Nishida et al 77 Hamasaki et al, 78 successfully showed, in organotypic cultures, the possibility of enhancing axon formation by magnetically localizing SPION-labeled cells.…”
Section: Tracking Stem Cells With Superparamagnetic Iron Oxide Nanopamentioning
confidence: 95%
“…Long-term success of certain surgical procedures still requires adjuvant therapy to enhance cell retention at a specific site. This can be achieved by labelling stem cells with superparamagnetic iron oxide nanoparticles (SPIONs) and applying a magnetic field to further guide their migration to sites requiring increased cell retention [70,71] (Figure 1D). Importantly, cell labelling with SPIONs appears not to affect viability, proliferation, or specification of MSCs into adipogenic, chondrogenic, or osteogenic lineages under in vivo conditions [72].…”
Section: Magnetic Actuation In the Regeneration Compartmentmentioning
confidence: 99%